Advances in clinical chemistry. - Makowski, Gregory S. (Gregory Stephen) (Academic Press, 2023)
Advances in Clinical Chemistry, Volume 112 highlights new advances in the field, with this new volume presenting interesting chapters on a variety of timely topics, including Heterogeneity in Major Depressive Disorder: The need for Biomarker-based and Personalized Treatments, Advances in exosome analysis, Translational Proteomics and Phosphoproteomics: Tissue to Extracellular Vesicles, Immune Checkpoint Therapy, Tumor Immunology, and Biomarkers in Non-Small-Cell Lung Cancer, Advances in Congestive Heart Failure Biomarkers, Fluid biomarkers in Alzheimer's disease, and more. Provides the most up-to-date technologies in clinical chemistry and clinical laboratory science ; Authored by world renowned clinical laboratory scientists, physicians and research scientists ; Presents the international benchmark for novel analytical approaches in the clinical laboratory.